Theory and Analysis of Impulsive Type Pantograph Equations with Katugampola Fractional Derivative - Vivek, D.; Harikrishnan, K. Kanagarajan, S. (Journal of Vibration Testing and System Dynamics, 2026)
In this paper, we investigate the existence, uniqueness and Ulam stability of solutions for impulsive type pantograph equations with Katugampola fractional derivative. The arguments are based upon the Banach contraction principle and Schaefer’s ﬁxed point theorem.